2015
DOI: 10.1117/1.jmi.2.4.043504
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of beam quality for photon-counting spectral computed tomography in head imaging: simulation study

Abstract: Abstract. Head computed tomography (CT) plays an important role in the comprehensive evaluation of acute stroke. Photon-counting spectral detectors, as promising candidates for use in the next generation of x-ray CT systems, allow for assigning more weight to low-energy x-rays that generally contain more contrast information. Most importantly, the spectral information can be utilized to decompose the original set of energy-selective images into several basis function images that are inherently free of beam-har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 53 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…tissue with a small cross-section diameter, such as in children (12,54), contrast media with higher atomic number and higher k-edge energies, such as gadolinium or targeted nanoparticles, may be better suited for performing imaging studies in large patients (12,48,49,55).…”
Section: Spatial Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…tissue with a small cross-section diameter, such as in children (12,54), contrast media with higher atomic number and higher k-edge energies, such as gadolinium or targeted nanoparticles, may be better suited for performing imaging studies in large patients (12,48,49,55).…”
Section: Spatial Resolutionmentioning
confidence: 99%
“…Examples include gold and platinum (86,87); xenon, bismuth, lutetium, tungsten, silver, and ytterbium could also be evaluated for use in photon-counting CT (88). Chen et al (55) showed that, with similar molar concentrations of gadolinium and iodine, the signal (in terms of squared signal difference-to-noise ratio normalized by skin dose) with gadolinium is three to 10 times higher than that with iodine. However, the clinically acceptable doses of gadolinium are lower compared with iodine doses.…”
Section: Contrast Agentsmentioning
confidence: 99%
“…Several studies have been published on how to model the frequency‐dependent detective quantum efficiency of photon‐counting detectors, but these studies do not take energy information into account. At the same time, the impact of detector nonidealities on spectral imaging tasks has been studied by several authors . However, these publications only study the zero‐spatial‐frequency performance and do not investigate the frequency‐dependent spectral performance.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the impact of detector nonidealities on spectral imaging tasks has been studied by several authors. [21][22][23][24][25][26][27] However, these publications only study the zero-spatial-frequency performance and do not investigate the frequency-dependent spectral performance. Shikhaliev et al 28 studied the effect of characteristic x rays on the spectrum shape and on the spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Tabulated or computer-generated x-ray spectra are useful for computer simulations pertaining to modeling of beam shaping filter performance, 1,2 imaging performance modeling, [3][4][5][6] validation of x-ray spectral measurements, 7-9 radiation dose, 10,11 modeling of photon counting spectral/dual-energy imaging systems, 8,[12][13][14] and many other applications. Recently, a tungsten anode spectral model using interpolating cubic splines (TASMICS 15 ) was proposed to update the previous tungsten anode spectral model using interpolating polynomials (TASMIP 16 ).…”
Section: Introductionmentioning
confidence: 99%